2018
DOI: 10.1186/s13256-018-1665-4
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo hemorrhagic fever with hepatic impairment and vaginal hemorrhage: a case report

Abstract: BackgroundCrimean-Congo hemorrhagic fever is a tick-borne disease described in more than 30 countries in Europe, Asia, and Africa. Albania is located in the southwestern part of the Balkan Peninsula. In 1986, the first case of Crimean-Congo hemorrhagic fever was registered, and cases of patients with hemorrhagic fever are rising, and most of them present in a serious condition, when the mortality rate is very high. In districts like Mirdite, Lezhe, Gjirokaster, Skrapar, Erseke, and Kukes, there is delineated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The trend of ALT in this case series highlights that a declining pattern of ALT has a good prognostic value compared to the actual level of ALT at presentation. Our results are parallel with the observations by Ayatollahi et al from Iran and Muco et al from Albania, who found a steep decline in the ALT among the survivors [ 15 , 16 ]. However, the non-survivors were not reported for comparison in the aforementioned case series.…”
Section: Discussionsupporting
confidence: 92%
“…The trend of ALT in this case series highlights that a declining pattern of ALT has a good prognostic value compared to the actual level of ALT at presentation. Our results are parallel with the observations by Ayatollahi et al from Iran and Muco et al from Albania, who found a steep decline in the ALT among the survivors [ 15 , 16 ]. However, the non-survivors were not reported for comparison in the aforementioned case series.…”
Section: Discussionsupporting
confidence: 92%
“…However, that study included a small patient sample size and none of the patients developed severe disease. Hepatic injury may also contribute to neurological impairment and one case reported the development of hepatic encephalopathy [66].…”
Section: Human Crimean-congo Hemorrhagic Fevermentioning
confidence: 99%